Effect of atrial fibrillation duration on plasma von Willebrand factor level. (16th October 2017) - Wysokinski, Waldemar E.; Cohoon, Kevin P.; Konik, Ewa A.; Melduni, Rowlens M.; Ammash, Naser M.; Asirvatham, Samuel J.; McBane, Robert D.
Abstract: Aims: von Willebrand factor (VWF) is an independent risk factor for adverse events in patients with non‐valvular atrial fibrillation (NVAF). However, it is unclear if VWF level remains elevated and predictive of stroke during entire course of NVAF. Methods and Results: In order to determine if VWF is a time‐dependent blood variable, VWF antigen measured by latex immunoassay in 425 NVAF patients and 100 controls with normal sinus rhythm (NSR) was analyzed according to NVAF duration (<1 month: n = 76, 1‐12 months: n = 98, and >12 months: n = 251). The mean VWF antigen level in NVAF patients with <1‐month duration (167 ± 59%) was not different compared to those with 1‐12 months (157 ± 50%, P  = .24) and >12 months duration (156 ± 54%, P  = .11) but higher compared to NSR controls (143 ± 48%, P  = .003). Higher VWF level correlated with higher CHADS2 scores and with progressing intensity of blood stasis in the left atrium and thrombus formation in all three time periods of atrial fibrillation duration. Patients not treated with warfarin had VWF 30% higher in the first month compared to following months. Conclusions: von Willebrand Factor is steadily elevated throughout the course of dysrhythmia in NVAF patients treated with warfarin and in those with higher intensity of left atrium blood stasis.